Trillions and Trillions: Herpes Simplex Virus–1 Hepatitis in an Immunocompetent Adult. (5th November 2019) - Ikuta, Kevin; Roychoudhury, Pavitra; Xie, Hong; Mcclurkan, Christopher L; Walkiewicz, Magdalena; Makhsous, Negar; Huang, Meei-Li; Beru, Yodit; Alam, Mariam; Shepherd, Amanda; Lamotte, Eric D; Patel, Kevin; et al.
Abstract: We describe a case of acute liver failure and myopericarditis due to herpes simplex virus–1 (HSV-1) in an immunocompetent adult. We estimate that, at the height of viremia, the patient contained a quantity of HSV-1 virions approaching that of human cells. The patient recovered with acyclovir that was dose-adjusted for neurotoxicity and developed a vigorous anti-HSV-1 T-cell response.